Gender perspectives in civil law - Álvarez Olalla, Pilar (EUNOMÍA. Revista en Cultura de la Legalidad, 2023)
Civil Law, as a branch of the legal system that regulates the most essential aspects of individuals, is especially sensitive to the influence that gender perspective must have on the reform of institutions traditionally regulated by laws resulting from patriarchal, sexist and discriminatory conceptions, mainly in family Law but also in the field of civil and commercial contracts and in the field of civil liability.
Keywords: Civil Law; discrimination; equality; shared custody; civil liability; gender violence